Ready for the euro? The case of Croatia and Bulgaria - Zoltan Walko (Oesterreichische Nationalbank (OeNB), 2022)
In this paper, I reflect on selected economic and institutional indicators of Croatia and Bulgaria ahead of the countries' potential adoption of the euro in 2023 and 20243, respectively. Our aim is to assess potential benefits and risks from the perspective of (1) the two countries and (2) the euro area. The adoption of the euro is neither a privilege nor an option. It is an obligation of each EU member state, as laid down in the Treaty on the Functioning of the European Union (TFEU) as soon as a member state sustainably fulfills the convergence criteria. For some countries, euro adoption will represent a significant change in the operating environment of their economies and in the conduct of their economic policies; for others it is a "logical" continuation of the existing monetary policy regime. I would like to emphasize that any assessment of "readiness" for euro adoption can only be a snapshot at a certain point in time: national political preferences and balances of power can change rapidly with an impact on national economic policies. It goes without saying that smooth and successful participation in the common currency area requires not only a thorough convergence assessment in line with the requirements of the TFEU, but also the continuation of sound economic policies upon euro adoption. This has to be supported by a euro area-/EU-wide institutional framework which allows for the timely detection of emerging threats for stability and which provides for effective tools to have these threats reversed. Further, this framework needs to strike a balance between adapting to evolving circumstances and at the same time applying the principal of equal treatment, as it has been applied by the European Commission and the European Central Bank (ECB) in Convergence Reports over the past 25 years. (...)
Keywords: 330; Euro; Eurozone; Konvergenzkriterien; Wirtschaftslage; Kroatien; Bulgarien